Dari Kali Code ke Ruang Digital: Meneguhkan Filsafat Memanusiakan Manusia Romo Mangun sebagai Etika Publik Generasi Kontemporer - Yanto Yanto (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2026)
Many of the ethical and sustainability challenges we face today, from the environmental crisis to the impacts of digital disruption, share a common root: we often compartmentalize nature, humanity, and technology. This complex problem demands a perspective that views everything as interconnected. This qualitative research aims to analyze the urgency of Integral Ecology as a transformative ethical framework and to ground it in the Pancasila Philosophy as a foundation in the Digital Age. I highlight the figure and thought of Father Y.B. Mangunwijaya as a practical model for implementing Social Ecology and Human Rights (HR). Using a literature review and philosophical analysis method, this research addresses three main questions. First, how does the concept of Integral Ecology bridge the environmental crisis and digital disruption? Second, what are the core moral values of Pancasila that must be applied in Public Ethics? Third, how can Father Mangun's spirit of "humanizing humanity" be expanded to "humanize all creation" in the technological era? The results indicate that the current sustainability crisis necessitates a holistic understanding, where environmental degradation is also a form of social injustice. Three core moral imperatives are derived from the Pancasila perspective. First, technological advancement must always be subordinate to the Humanity principle (Sila Kemanusiaan) to safeguard the dignity of both humanity and nature. Second, Public Ethics must integrate ecological responsibility as a component of social justice. Third, the younger generation must actively participate in pro-environmental democratic efforts, inheriting the spirit of Father Mangunwijaya. In summary, Integral Ecology grounded in Pancasila offers an essential ethical roadmap for shaping the current generation's critical awareness towards technology and the environment in a balanced manner.AbstrakBanyak masalah etika dan keberlanjutan yang kita hadapi saat ini, mulai dari krisis lingkungan hingga dampak gejolak digital, berakar pada satu hal, kita sering memisahkan alam, manusia, dan teknologi. Permasalahan ini sangat rumit sehingga menuntut cara pandang yang melihat semuanya terhubung. Penelitian kualitatif ini bertujuan untuk menganalisis betapa mendesaknya Ekologi Integral sebagai kerangka etika yang transformatif dan menjadikannya berlandaskan pada Filsafat Pancasila sebagai pijakan di era digital. Saya mengangkat sosok dan pemikiran Romo Y.B. Mangunwijaya sebagai model nyata bagaimana mempraktikkan Ekologi Sosial dan Hak Asasi Manusia (HAM). Dengan menggunakan metode studi pustaka dan analisis filosofis, penelitian ini menjawab tiga pertanyaan utama. Pertama, bagaimana konsep Ekologi Integral menjembatani krisis lingkungan dan disrupsi digital. Kedua, apa nilai moral utama Pancasila yang harus diterapkan dalam Etika Publik. Ketiga,  bagaimana semangat Romo Mangun "memanusiakan manusia" dapat diperluas untuk "memanusiakan seluruh ciptaan" di era teknologi. Hasil penelitian menunjukkan bahwa krisis keberlanjutan saat ini membutuhkan pemahaman holistik, di mana kerusakan lingkungan adalah juga bentuk ketidakadilan sosial. Ditemukan tiga perintah moral utama dari perspektif Pancasila. Pertama, kemajuan teknologi harus selalu berada di bawah kendali Sila Kemanusiaan demi menjaga martabat manusia dan alam. Kedua, etika Publik wajib mengintegrasikan tanggung jawab ekologis sebagai bagian dari keadilan sosial. Ketiga,  generasi muda mesti berpartisipasi aktif dalam upaya demokrasi yang pro-lingkungan, mewarisi semangat Romo Mangunwijaya. Singkatnya, Ekologi Integral yang berlandaskan Pancasila menawarkan peta jalan etika yang sangat penting untuk membentuk kesadaran kritis generasi sekarang terhadap teknologi dan lingkungan secara seimbang.